Synergy of the Pentahelix Model to Establish Resilient Smes in Facing New Normal during Covid-19 Pandemic - Herdiana Dyah Susanti; Dian Arief Pradana; Endang Suprihatin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Coronavirus new which caused the outbreak of pneumonia and caused the closure of tourist destinations and caused many SMEs products to be returned by the souvenir center and SMEs production stopped during the Covid-19 pandemic. Banyuwangi Regency has also experienced the closure of tourist destinations starting March 2020 and has an impact on SMEs in Banyuwangi Regency, one of which is Ratu Manis SMEs. After the closure of tourist attractions, 70% of Ratu Manis SMEs products that were entrusted to the souvenir center and tourist attractions were returned. The number of SMEs Ratu Manis production has also decreased. Many exhibition events at every festival held in Banyuwangi Regency have been canceled due to the Covid-19 pandemic. Ratu Manis SMEs is trying to rise from the impact caused by the Covid-19 pandemic through synergy from various parties with the help of the government, academics, media and the community using the pentahelix approach. The research approach used in this research is descriptive research. The data sources used in this study are secondary and primary data sources. The data were collected using data collection techniques, namely observation and interviews with the source triangulation strategy for data validity. With penta helix synergy of industry, government, academia, media and the community sweet queen SMEs can survive to face the pandemic covid-19 and may even improve the quality of the products and sales turnover also increased from 20 kg to 40 kg per day.